'It might hurt, but you have to push through the pain': Perspectives on physical activity from children with juvenile idiopathic arthritis and their parents. (December 2016) - Race, Douglas L; Sims-Gould, Joanie; Tucker, Lori B; Duffy, Ciaran M; Feldman, Debbie Ehrmann; Gibbon, Michele; Houghton, Kristin M; Stinson, Jennifer N; Stringer, Elizabeth; Tse, Shirley ML; McKay, Heather A
Our primary objective was to gather perspectives of children diagnosed with juvenile idiopathic arthritis (JIA) and their parents as they relate to physical activity (PA) participation. To do so, we conducted a study on 23 children diagnosed with JIA and their parents ( N = 29). We used convenience sampling to recruit participants and qualitative method- logies (one-on-one semi-structured interviews). We adopted a five-step framework analysis to categorize data into themes. Children and their parents described factors that act to facilitate or hinder PA participation. Pain was the most commonly highlighted PA barrier described by children and their parents. However, children who were newly diagnosed with JIA and their parents were more likely to highlight pain as a barrier than were child/parent dyads where children had been previously diagnosed.